Fulminant pseudomembranous enterocolitis caused by Klebsiella oxytoca: an autopsy case report. Issue 1 (24th October 2018) - Nagamura, Tatsunori; Tanaka, Yoshihiro; Terayama, Takero; Higashiyama, Daishi; Seno, Soichiro; Isoi, Naoaki; Katsurada, Yuka; Matsubara, Akiko; Yoshimura, Yuya; Sekine, Yasumasa; Akitomi, Shinji; Sato, Kimiya; et al.
Abstract : Case: We describe a rare case of antibiotic‐associated fulminant pseudomembranous enterocolitis caused by Klebsiella oxytoca . A 79‐year‐old man with a history of antibiotic therapy was admitted to our emergency department, complaining of consciousness disturbance. Initially, we suspected septic shock and diabetic ketoacidosis caused by intestinal infection. Although we administered sufficient extracellular fluid, his blood pressure was not elevated and his abdomen gradually swelled. Outcome: The patient died of shock and abdominal compartment syndrome. Autopsy revealed widespread jejunal necrosis in conjunction with colitis, suggesting fulminant pseudomembranous enterocolitis caused by K. oxytoca infection. Conclusion: As the clinical features of pseudomembranous enterocolitis caused by K. oxytoca resemble the features of colitis caused by Clostridium difficile, conservative therapy is applied first. However, fulminant pseudomembranous enterocolitis is a lethal disease, necessitating early operation for resection of the necrotic lesion. This report highlights the need for better surgical criteria at an early stage. Abstract : A 79‐year‐old man with a history of antibiotic therapy was admitted to our emergency department, complaining of consciousness disturbance. He died of shock and abdominal compartment syndrome, and autopsy revealed fulminant pseudomembranous colitis caused by Klebsiella oxytoca infection. Fulminant pseudomembranous colitis is lethal and early operation is necessary if it is suspected.